2020
DOI: 10.3892/mmr.2020.11688
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‑specific deletion of natriuretic peptide receptor A induces differential myocardial expression of circular RNA and mRNA molecules involved in metabolism in mice

Abstract: Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are important biological markers and regulators of cardiac function. The natriuretic peptide receptor A (NPRA), also known as NPR1 or guanylyl cyclase A, binds ANP and BNP to initiate transmembrane signal transduction by elevating the intracellular levels of cyclic guanosine monophosphate. However, the effects and mechanisms downstream of NPRA are largely unknown. The aim of the present study was to evaluate the changes in the global pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It is reported that NPRA-deficient mice have low mRNA and protein expression (17,18). Our previous study (9) aslo confirmed that the expression in mRNA and protein of NPRA decreased in the cardiac tissues of the mice.…”
Section: Npra-deficient Mice Have Distinct Metabolic Patterns Compared With Control Micesupporting
confidence: 77%
See 1 more Smart Citation
“…It is reported that NPRA-deficient mice have low mRNA and protein expression (17,18). Our previous study (9) aslo confirmed that the expression in mRNA and protein of NPRA decreased in the cardiac tissues of the mice.…”
Section: Npra-deficient Mice Have Distinct Metabolic Patterns Compared With Control Micesupporting
confidence: 77%
“…All experimental protocols included in this manuscript were approved by the local animal care committee. In the previous research of the group, we have obtained myocardial-specific NPRA knockout mice (9). So we used the mice with cardiomyocyte-specific deletion of NPRA (NPRA flox/flox : Myh6-Cre mice) as in the previous study.…”
Section: Animalsmentioning
confidence: 99%
“…In our research, the methodology of CRISPR/Case 9 to generate the gene-ablated mice and the NPRA deletion figure were published previously. 27…”
Section: Methodsmentioning
confidence: 99%
“…And the mice with genotype NprA flox/flox could also be used as control mice (NPRA +/+ ). 27 To achieve tissue-specific deletion of the NPRA gene, NprA flox mice were crossed with CKMM-Cre transgenic mice (Shanghai Model Organisms Center, Inc.) to obtain NprA flox/flox /CKMM-Cre mice. In NprA flox/flox /CKMM-Cre mice, the NPRA gene was specifically disrupted in the myocardium.…”
Section: Generation Of Mice With Cardiac-specific Inactivation Of Npramentioning
confidence: 99%
See 1 more Smart Citation